Principles of taxation for business and investment planning / Sally M. Jones, Shelley C. Rhoades-Catanach - Jones, Sally M.
Principles of Taxation for Business and Investment Planning focuses on the role taxes play in business and investment decision, presenting the general roles of taxation and discussing its implications for all tax-paying entities before delving into a specific exception. The benefit of this approach is a strong grasp of the fundamental principles informing taxation rules: students comprehend the framework of the tax system, making future changes to the tax code easier to understand-no matter how many there are.